(untitled) (Journal of Management and Social Sciences, 2024)
Abstract Political clientelism, locally known as godfatherism has been a recurring issue in the democratic practice of developing countries. It has become a key feature of Nigeria’s democratic practice and has been adjudged by several literature as a bane towards good governance. The work focuses on the effects of godfatherism as well as the perceptions of the citizens of Kwara State, a State which has had a long history of acts of godfatherism in Nigeria and one which the citizens in the 2019 General elections denied the wishes of the godfathers with their votes. The study was conducted using a descriptive survey method, using questionnaire as a means of data collection from 385 Krejcie and Morgan samples in the state. The data was analysed using a regression model. The study found significant impact of godfatherism on governance in Kwara State and recommends the need to curb godfatherism for improved democratic practice. Keywords Godfatherism, politics, democracy, governance, Kwara State, Nigeria